KONSTRUKSI SOSIAL KONSEP CANTIK PADA REMAJA DI KOTA TANJUNGPINANG - Shania Desvianty; Siti Arieta; Sri Wahyuni (JURNAL SOSIO-KOMUNIKA, 2024)
Skin care are a social reality that has mushroomed in social life, not only the upper age layer but also the lower age layer often use skin care. This society is synonymous with adolescence as seen from the status of those who are still in school due to the role of social media and also influencer reviewers, thus creating construction social media in the use of skin care by teenagers. The research entitled Social Construction of Beautiful Consept Adolescents in Tanjungpinang City. In order to be able to answer this problem, the theory put forward by Peter L. Berger is Construction Social. Among other things, by using the social definition paradigm by using qualitative research methods with a descriptive approach. The data collection techniques in this study used observation data collection techniques, interviews, and documentation. In this study there were 10 people as informants with purposive sampling technique. This study does not blame the use of skin care as a right or wrong behavior, but this research explains how to use skin care according to age, safety in use, avoiding extravagant living, so it doesn't change the meaning of beauty.